Cutting‐edge mass spectrometry characterization of originator, biosimilar and biobetter antibodies. (2nd February 2015) - Beck, Alain; Debaene, François; Diemer, Hélène; Wagner‐Rousset, Elsa; Colas, Olivier; Dorsselaer, Alain Van; Cianférani, Sarah
Abstract : The approval process for antibody biosimilars relies primarily on comprehensive analytical data to establish comparability and high similarity with the originator. Mass spectrometry (MS) in combination with liquid chromatography (LC) and electrophoretic methods are the corner stone for comparability and biosimilarity evaluation. In this special feature we report head‐to‐head comparison of trastuzumab and cetuximab with corresponding biosimilar and biobetter candidates based on cutting‐edge mass spectrometry techniques such as native MS and ion‐mobility MS at different levels (top, middle and bottom). In addition, we discuss the advantages and the limitations of sample preparation and enzymatic digestion, middle‐up and ‐down strategies and the use of hydrogen/deuterium exchange followed by MS (HDX‐MS). Last but not least, emerging separation methods combined to MS such as capillary zone electrophoresis‐tandem MS (CESI‐MS/MS), electron transfer dissociation (ETD), top down‐sequencing (TDS) and high‐resolution MS (HR‐MS) that complete the panel of state‐of‐the‐art MS‐based options for comparability and biosimilarity evaluation are presented. Copyright © 2015 John Wiley & Sons, Ltd.